Optimal selection method for investment project - Žilinskas, Vytautas Jonas (Business, Management and Economics Engineering, 2010)
Under the modern world market conditions the investment activity of enterprises is increasing. Therefore, one of the main aspects of the investment activity guarantee is a selection and apprehension of the main principles of the investment control and possi-bilities of different uses of the investment instruments. For the optimum selection of the investment projects it is suggested to use a formalistic experimental author’s modified method of priority allocation and selection, which gives an opportunity to evaluate the investment project according to different partial criteria and their meaning of importance. Working out this way a complex evaluation of each chosen investment project is obtai-ned. Using the suggested MPSP (modified method of priority allocation and selection) the investment projects are evaluated with qualitative and quantitative criteria. So this method can be used when qualitative criteria of evaluation are predominated. Formalis-tic methods of analysis cannot be used to establish quantitative criteria and those small projects when it is relatively too expensive to apply other usual methods of the financial economic analysis. Method MPSP selection is universal and ordinary so it can be used to establish the efficiency of different projects, to classify projects, to model the strategy of the state economy. If you like to control the realization of the chosen investment project more effectively and rationally it is suggested to use PERT (Program Evaluation and Review Technique).The main control elements of the investment project are reviewed in the article using PERT which is useful to draw up an optimistic reticular schedule of the investment work implementation. Article in Lithuanian. Investicinių projektų optimalios atrankos metodas